Students’ Social Representations of Forced Migration as a Relevant Social Problem and Its Curricular Inclusion at the End of Primary School - Roberto García-Morís (MDPI AG, 2021)
The purpose of this paper is to assess students’ social representations of forced migration as a relevant social problem in the last year of primary education and the opportunity for its curricular inclusion. The study was carried out by means of a questionnaire, filled in by 6th-year primary education groups (11–12 years old) (n = 70), in a state-supported private school in the city of A Coruña (Galicia, Spain). The questionnaire was supported by three pictures of forced migrations from the media. In this case, the children had to interpret the pictures through a series of questions that sought to investigate their representations, the causes they identify in this social problem, their opinions, and possible solutions. Finally, the opportunity for the inclusion of social problems as curriculum content was addressed. The study shows that the students are in favor of migrants, that they use concepts from the social sciences in their arguments—albeit simple ones, and that they are in favor of the curricular inclusion of social problems, in which they develop representations through different sources of information.